2001
DOI: 10.1177/089686080102100221
|View full text |Cite
|
Sign up to set email alerts
|

Does Enalapril Prevent Peritoneal Fibrosis Induced by Hypertonic (3.86%) Peritoneal Dialysis Solution?

Abstract: Objective Peritoneal fibrosis (PF) is one of the most serious causes of failure in continuous ambulatory peritoneal dialysis (PD). Although the underlying mechanism responsible for the genesis of PF is still unknown, transforming growth factor p (TGFβ1) has been shown to be associated with PF. Angiotensin converting enzyme inhibitors have been shown to prevent the stimulating effect of growth factors. The aim of the present study was to investigate the effect of enalapril on peritoneal function and morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 20 publications
4
61
0
1
Order By: Relevance
“…In the Study of Duman et al, [40] the used of lisinopril in peritoneal fibrosis of rat showed that there was a significant decrease in TGF-β expression (p<0.05), while on histologic examination showed peritoneum fibrosis reduction compared to dextrose group but it was not statistically significant (p>0.05). In another study, Duman et al [4] used another ACEI like enalapril, obtained high TGF-β results in the CAPD group, undetectable in the control group and CAPD+enalapril (p=0.01) fibroblast peritoneum decreased in CAPD+enalapril compared to CAPD (p>0.05).…”
Section: Tgf-β Expression and Fibrosis Peritoneummentioning
confidence: 97%
See 3 more Smart Citations
“…In the Study of Duman et al, [40] the used of lisinopril in peritoneal fibrosis of rat showed that there was a significant decrease in TGF-β expression (p<0.05), while on histologic examination showed peritoneum fibrosis reduction compared to dextrose group but it was not statistically significant (p>0.05). In another study, Duman et al [4] used another ACEI like enalapril, obtained high TGF-β results in the CAPD group, undetectable in the control group and CAPD+enalapril (p=0.01) fibroblast peritoneum decreased in CAPD+enalapril compared to CAPD (p>0.05).…”
Section: Tgf-β Expression and Fibrosis Peritoneummentioning
confidence: 97%
“…Angiotensin II is considered a growth factor that has a role in cell proliferation, apoptosis, and fibrosis. ACEI that are working with the inhibition of angiotensin II will decrease proteinuria, inflammatory cell infiltration, fibrosis, and growth factor [4,32,33].…”
Section: Putranto Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…In experimental animal models, therapy with ACEi was proven to slow the morphological peritoneal membrane alterations associated with glucose exposure through the decrement in angiogenesis and fibrosis (3,4,21). Beneficial effects of RAAS-blocking drugs on peritoneal transport characteristics were also reported in patients treated with PD (3,11,14,15). It was demonstrated that RAAS-blocking drugs prevent the increase in small solute transport, which is probably related to a lower number of peritoneal blood vessels and less fibrosis (3).…”
Section: A Trošt Rupnik Et Al 428mentioning
confidence: 99%